Deux grandes dames : Bertha Wilson et Claire L'Heureux-Dube a la Cour Supreme du Canada - Backhouse, Constance, 1952- (Les Presses de l'Universite d'Ottawa, 2021)
"Bertha Wilson and Claire L'Heureux-Dubé were the first women judges on the Supreme Court of Canada. Their 1980s judicial appointments delighted feminists and shocked the legal establishment. Polar opposites in background and temperament, the two faced many identical challenges. Constance Backhouse's compelling narrative explores the sexist roadblocks both women faced in education, law practice, and in the courts. She profiles their different ways of coping, their landmark decisions for women's rights, and their less stellar records on race. To explore the lives and careers of these two path-breaking women is to venture into a world of legal sexism from a past era. The question becomes, how much of that sexism has been relegated to the bins of history, and how much continues?"--Amazon.com.